2018
DOI: 10.2147/cia.s162899
|View full text |Cite
|
Sign up to set email alerts
|

AKI in the very elderly patients without preexisting chronic kidney disease: a comparison of 48-hour window and 7-day window for diagnosing AKI using the KDIGO criteria

Abstract: ObjectivesTo compare the differences between the Kidney Disease Improving Global Outcomes (KDIGO) criteria of the 48-hour window and the 7-day window in the diagnosis of acute kidney injury (AKI) in very elderly patients, as well as the relationship between the 48-hour and 7-day windows for diagnosis and 90-day mortality.Patients and methodsWe retrospectively enrolled very elderly patients (≥75 years old) from the geriatrics department of the Chinese PLA General Hospital between January 2007 and December 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
1
6
0
1
Order By: Relevance
“…Usually the term ‘‘elderly’’ denotes broadly older individuals, but there is not universally accepted definition or cut-off age. Indeed, many authors have proposed various ages ranging from 60 years (indicated as elderly) to >80 years (indicated as very elderly) in the attempt to define the aged status [ 15 , 16 , 17 ]. Currently, it is reasonable to call “elderly” a patient with age >65 years.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the term ‘‘elderly’’ denotes broadly older individuals, but there is not universally accepted definition or cut-off age. Indeed, many authors have proposed various ages ranging from 60 years (indicated as elderly) to >80 years (indicated as very elderly) in the attempt to define the aged status [ 15 , 16 , 17 ]. Currently, it is reasonable to call “elderly” a patient with age >65 years.…”
Section: Introductionmentioning
confidence: 99%
“…O envelhecimento populacional e acúmulo de comorbidades interferem na taxa de filtração glomerular (TFG)/ Clearance de Creatinina (ClCr), o que tem predisposto nos últimos anos ao aumento da incidência de LRA (16,17) . O envelhecimento natural oferece modificações na estrutura e função renal, a exemplo da esclerose glomerular e fibrose intersticial, que podem culminar na lesão renal propriamente dita (11,18) e tender à progressão para a cronicidade, doença renal em estágio final e morte (19) , como identificado neste estudo.…”
Section: Discussionunclassified
“…The recovery of renal function was defined as no less than a 1.0-fold decrease from baseline serum creatinine level within 1 week after AKI. 23) We corrected the p value by Bonferroni's correction. The corrected p values were set at 0.025 (0.05 divided by 2) assuming that two intergroup analyses were conducted.…”
Section: Study Design and Patient Eligibilitymentioning
confidence: 99%